Factors Affecting the Attitude of Travel Agents towards Use Of the Web to Market Travel Insurance Products in China - Zhou, Sophie Feng (2013)
In 2012, the total revenue contributed by tourism industry achieved 2.59 trillion Yuan with an increase of 15.2 percent over last year. The steady and stable development of tourism industry serves a solid foundation for the boost of travel insurance industry. Every insurance company and its partner in the distribution channel show their aggressiveness in exposing travel insurance products by use of marketing tools, but it is not prevalent in use as much as possible among travel agencies in China, who are the targets of this study. This author aims to put an emphasis on travel agents and spares on effort to seek the factors affecting their attitude toward marketing travel insurance products via Internet. A quantitative approach is used to explore the factors based on a return of 97 responses. According to data analysis, three variables out of seven variables constructing the hypotheses are supported. The research shows the internet can be used as an extremely effective channel for marketing travel insurance products but this requires extensive knowledge pertaining to consumers.